2019
DOI: 10.1002/ptr.6472
|View full text |Cite
|
Sign up to set email alerts
|

Paeonol ameliorates monosodium urate‐induced arthritis in rats through inhibiting nuclear factor‐κB‐mediated proinflammatory cytokine production

Abstract: Moutan Cortex has been widely used to treat various types of arthritis in traditional Chinese medicine. Paeonol is isolated as an active ingredient from Moutan Cortex. However, the effect and potential mechanism of paeonol on gouty arthritis have not been evaluated. In this study, rats were treated intragastrically with paeonol for consecutive 7 days. On Day 5, rats were intra‐articularly injected with monosodium urate (MSU) crystals in the ankle joints to induce MSU‐induced arthritis (MIA). Paw volume was det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
(46 reference statements)
0
18
0
Order By: Relevance
“…The current results showed that paeonol exerted anti‐inflammatory effects on IR testes by downregulating TNF‐α gene expression as well as IL‐1β and IL‐6 protein expression. Paeonol displayed the same anti‐inflammatory effects in monosodium urate‐induced arthritis in rats (Chen et al, 2019) and lipopolysaccharides‐induced acute lung injury in mice (Wang, Zhu, et al, 2019). Moreover, paeonol protected against endoplasmic reticulum stress‐associated inflammation in lead‐stimulated kidneys (Liu et al, 2018) and IL‐1β‐induced inflammatory response in human primary chondrocytes (Wang, Xu, Kang, Zhang, & Li, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…The current results showed that paeonol exerted anti‐inflammatory effects on IR testes by downregulating TNF‐α gene expression as well as IL‐1β and IL‐6 protein expression. Paeonol displayed the same anti‐inflammatory effects in monosodium urate‐induced arthritis in rats (Chen et al, 2019) and lipopolysaccharides‐induced acute lung injury in mice (Wang, Zhu, et al, 2019). Moreover, paeonol protected against endoplasmic reticulum stress‐associated inflammation in lead‐stimulated kidneys (Liu et al, 2018) and IL‐1β‐induced inflammatory response in human primary chondrocytes (Wang, Xu, Kang, Zhang, & Li, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Paeonol, a phenolic active constituent isolated from the genus Paeonia , possesses remarkable antioxidant and anti-inflammatory effects, which are beneficial in many diseases, such as gastric ulcer [ 15 ], hypertension [ 16 ], arthritis [ 17 ], and epilepsy [ 18 ]. Recently, we have demonstrated that paeonol can also protect against testicular ischemia-reperfusion injury [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Pharmacological evidence suggests that paeonol has antibacterial, antiaggregation, antianxiety, and antiinflammation effects. 8,[10][11][12][13][14] In fact, unlike single chemical entities aimed at a specific single target, traditional Chinese medicines are complex mixtures containing hundreds of diverse chemical constituents. 15 Therefore, traditional Chinese medicines are too complicated to investigate comprehensively their quality consistency effectively with a single detection technique.…”
mentioning
confidence: 99%